Multifunctionality of mas ‘but’ in Portuguese - Goreti Pezatti , Erotilde; Storti Garcia, Talita (Linguistik Online, 2023)
Hengeveld/Mackenzie (2008: 52) consider that the constructions with mas ‘but’ result from the combination of two Discursive Acts with different communicative statutes, there being a Nuclear Discursive Act, with greater communicative weight, and a Subsidiary Discursive Act, which will have a rhetorical function named “Concession”. This paper aims to investigate the various uses of mas ‘but’, according to Functional Discourse Grammar, in order to determine the pragmatic, semantic, and morphosyntactic properties of each case in real occurrences of Portuguese. The combination of linguistic units through mas ‘but’ always indicates interpersonal strategies, which are differentiated by the communicative intention of the speaker as well as reflected in the layer involved. However, mas maintains the capacity to attribute the most salient status of information to the unit it scopes or operates on. We identified four uses of mas ‘but’ in different layers: Move Operator in the Move layer, Emphasis Operator and Concession rhetorical function in the Discursive Act layer, and the Contrast pragmatic function in the Communicated Content layer.